DISEASES OF THE GENITOURINARY SYSTEM IN HIV INFECTION–A NEW PROBLEM OF MODERN UROLOGY - S. K. Yarovoy (Исследования и практика в медицине)
The article presents the results of a retrospective analysis of the provision of urological care 352 HIV-infected patients in the Urological City Clinical Hospital №47 of Moscow Health Department for the period 1996–2012. We estimated of income dynamics of HIV-infected patients in urological hospital, studied the distribution of these patients for urological nosology and stage of HIV infection. We noted the predominance of acute infectious and inflammatory diseases of the genitourinary system, that require immediate initiation of antibiotic therapy in the empirical mode, and in some cases, emergency surgery. We detected the predisposition to acute infectious and inflammatory diseases of the scrotum is a feature of HIV-infected patients.Article is supplemented with analysis of the effectiveness of the main pharmacological groups of antibacterial drugs for the treatment of nonspecific infectious and inflammatory diseases of the urogenital system in patients with HIV infection.